International Migration, Capital Mobility and Transitional Dynamics. - Baldwin, R; Venables, A (1994)
The authors study interactions between goods trade and international factor mobility in a context suggestive of transition in Central and Eastern Europe. If complementarities between skilled labor and capital are strong--e.g., owing to externalities between skilled labor and costs of absorbing capital inflow--then there are multiple rational expectations equilibria. The 'virtuous' transition path has capital inflow and little emigration; the 'vicious' path involves significant emigration and little capital inflow. The equilibrium transition path is not socially optimal even absent externalities. Externalities associated with skilled labor increase the case for intervention; policy should be used to delete the vicious equilibrium.